Fuzzy event-triggered sliding mode depth control of unmanned underwater vehicles - Zhang, Xun; Yao, Sibo; Xing, Wen; Feng, Zhiguang (Ocean engineering, 2022)
This paper focuses on the problem of depth controller design of unmanned underwater vehicles (UUVs) subject to ocean currents and communication delays via a Takagi–Sugeno (T–S) fuzzy modeling method and an event-triggered integral sliding mode control strategy. An event-triggered scheme is developed to avoid unnecessary redundancy in terms of communication resources and an integral sliding mode control strategy is proposed to strength anti-interference ability of the vehicle in complex ocean currents. Sufficient conditions for the existence of a practical sliding mode and the stability of the sliding motion are established in the form of linear matrix inequalities (LMIs), under which the state trajectory is compelled to a bounded region near the sliding surface and moves along the surface toward the equilibrium point after finite time. Whether inter-execution time intervals have a positive lower bound is also analyzed and the absence of the Zeno effect in the designed event-triggered scheme is corroborated. Finally, simulation results and discussions are provided to verify the effectiveness of the new design techniques. •A T–S fuzzy model for an UUV subject to multiple practical constraints is constructed.•A robust depth control is designed based on an event-triggered integral SMC method.•Sufficient conditions are derived to achieve the desired performance for the system.